2016
DOI: 10.21699/jns.v6i1.483
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Plain Radiograph in Neonatal Intestinal Obstruction

Abstract: A comprehensive all-inclusive resource on plain radiograph in neonatal intestinal obstruction is presented. This is an attempt to develop a protocol and to regain expertise in evaluating a plain radiograph that most often yields more than enough clues to diagnose and to decide a plan of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…triangular or a semilunar collection of air anterior to the abdominal viscera or above the liver in lateral decubitus position, (c) large volume of free air may give rise to the football sign, where the air outlines the whole of the peritoneal cavity and under the surface of the diaphragm, (d) the lacing of the football i.e. outlining of falciparum ligament of the liver against the radiolucency of free abdominal air on supine view [4,5,6] (e) Rigler sign or double-wall sign is free gas on both sides of the bowel wall, [4,5] (f) pneumoscrotum has been explained due to presence of patent processus vaginalis and passage of air from the peritoneal cavity into the scrotum. [3,5,6] The clinical findings in pneumoperitoneum secondary to NEC or neonatal GI perforation include features of peritonitis, tense abdominal distension, palpable, distended bowel loops, shiny red induration of abdominal wall, tenderness, muscle stiffness, guarding, shifting dullness, and absent (decreased) bowel sounds.…”
Section: Discussionmentioning
confidence: 99%
“…triangular or a semilunar collection of air anterior to the abdominal viscera or above the liver in lateral decubitus position, (c) large volume of free air may give rise to the football sign, where the air outlines the whole of the peritoneal cavity and under the surface of the diaphragm, (d) the lacing of the football i.e. outlining of falciparum ligament of the liver against the radiolucency of free abdominal air on supine view [4,5,6] (e) Rigler sign or double-wall sign is free gas on both sides of the bowel wall, [4,5] (f) pneumoscrotum has been explained due to presence of patent processus vaginalis and passage of air from the peritoneal cavity into the scrotum. [3,5,6] The clinical findings in pneumoperitoneum secondary to NEC or neonatal GI perforation include features of peritonitis, tense abdominal distension, palpable, distended bowel loops, shiny red induration of abdominal wall, tenderness, muscle stiffness, guarding, shifting dullness, and absent (decreased) bowel sounds.…”
Section: Discussionmentioning
confidence: 99%
“…The plain abdominal radiographic findings of dilated small bowel greatly supported a diagnosis of intestinal obstruction. However, the possibility of minute perforation couldn't be excluded since he presented with additional features of peritonitis (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…A plain radiograph of abdomen continues to be a useful tool for the diagnosis of neonatal intestinal obstruction demonstrating distended bowel loop or double bubble in proximal obstruction secondary to duodenal atresia (8,9) The management of neonatal intestinal perforation depends on the aetiological factor and varies to include primary repair, resection and anastomoses, ileostomy, colostomy, gastrectomy and gastroduodenostomy (10)(11)(12). Though, Hiller et al reported neonates with ileal atresia who undergo primary resection and anastomosis had a better outcome than those who had secondary anastomosis, mortality and major complications are seen in neonates managed with primary anastomoses compared to ileostomy (13,14) Case description A four (4) day old neonate, born to a 21-year-old primiparous mother delivered at term with a birth weight of 2.30 kg was admitted as a referral from another health unit with failure to pass stool associated with abdominal distension, vomiting of non-bilious content and irritability since birth.…”
Section: Introductionmentioning
confidence: 99%
“…The index case demonstrated the classical soap bubble pattern of gas distribution seen in necrotising enterocolitis. The differential diagnoses of this soap bubble appearance in abdominal radiographs of a neonate are pneumatosis intestinalis (as part of necrotising enterocolitis) due to intramural bowel gas and meconium plug syndrome due to the air captured between the meconium pellets 3. Pneumatosis intestinalis is a pathognomonic radiological sign of necrotising enterocolitis.…”
Section: Descriptionmentioning
confidence: 99%